Faktor-Faktor Yang Mempengaruhi Perkembangan Koperasi Mahasiswa di Banjarmasin - Aslamiyah; Nasrudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The researcher conducted this research to look at factors that the number of members, own capital loan capital, and business volume jointly influence the success of the development of student Cooperatives in Banjarmasin and see the dominant factors influencing student growth cooperatives in Banjarmasin. Research that uses an analysis variable unit indicator consisting of variables that affect student cooperatives in Banjarmasin. Research shows the number of student Cooperatives registered at the Banjarmasin UKM and NAKER Cooperative Service in each subdistrict in Banjarmasin City which amounts to 7 (seven) units with an active number of 4 (four) units from all sub-districts and 3 (three) other companies that are active